Application of the Internet of Things in Information Resource Supply Chain Management: A Model for Information Centers in Iran - Siahsarani Salah ol Din Kola, Sedigheh; Zarei, Hajar; Toudar, Seyed Rasool (AI and Tech in Behavioral and Social Sciences, 2025)
The aim of this research is to present a model for the application of the Internet of Things (IoT) in the management of the information resource supply chain in information centers. This research is descriptive-analytical in terms of data collection method, and inductive-deductive in its approach. Participants were selected purposefully through interviews with 15 experts and specialists with extensive service experience and advanced academic degrees in the fields of management, computer science, information technology, and knowledge sciences, based in information centers and universities in Iran. The interviews continued until theoretical saturation was achieved with 12 participants. Using a documentary study (books, articles, and related research), the initial interview questions were developed. After gathering the written responses of the participants, the process of analyzing the explicit and latent content of the collected information from the statements and writings began. The aim of this process was to extract the components of IoT application in information resource supply chain management in information centers using a qualitative approach. For the analysis of interview texts, thematic analysis was employed based on Braun and Clarke's (2006) method with the assistance of MAXQDA software. From the analysis of 15 interviews, a total of 178 initial codes were extracted. After analyzing the interview texts, 49 basic themes and 11 organizing themes were identified. In the final stage, by examining the organizing themes, five overarching themes emerged, namely logistics, production, distribution, information management throughout the supply chain, and relationship management throughout the supply chain.